A clinical audit cycle of post‐operative hypothermia in dogs. (September 2016) - Rose, N.; Kwong, G. P. S.; Pang, D. S. J.
Abstract : OBJECTIVES: Use of clinical audits to assess and improve perioperative hypothermia management in client‐owned dogs. METHODS: Two clinical audits were performed. In Audit 1 data were collected to determine the incidence and duration of perioperative hypothermia (defined as rectal temperatures <37·0°C). The results from Audit 1 were used to reach consensus on changes to be implemented to improve temperature management, including re‐defining hypothermia as rectal temperature <37·5°C. Audit 2 was performed after 1 month with changes in place. RESULTS: Audit 1 revealed a high incidence of post‐operative hypothermia (88·0%) and prolonged time periods (7·5 hours) to reach normothermia. Consensus changes were to use a forced air warmer on all dogs and measure rectal temperatures hourly post‐operatively until temperature ≥37·5°C. After 1 month with the implemented changes, Audit 2 identified a significant reduction in the time to achieve a rectal temperature of ≥37·5°C, with 75% of dogs achieving this goal by 3·5 hours. The incidence of hypothermia at tracheal extubation remained high in Audit 2 (97·3% with a rectal temperature <37·5°C). CLINICAL SIGNIFICANCE: Post‐operative hypothermia was improved through simple changes in practice, showing that clinical audit is a useful tool for monitoring post‐operative hypothermia and improving patient care. Overall management of perioperative hypothermia could be further improved with earlier intervention.